Pengaruh Management Compensation, Pertumbuhan Pendapatan dan Firm Size Terhadap Tax Management : (Studi Empiris Pada Perusahaan Sektor Energy di Bursa Efek Indonesia Tahun 2019-2023) - Ayu Lestari, Sitinur; Fitria Eka Ningsih (Universitas Pamulang, 2025)
This study aims to analyze the effect of management compensation, revenue growth,and firm size on tax management in energy sector companies listed on the IndonesiaStock Exchange (IDX) during the 2019–2023 period. The research employed apurposive sampling method, resulting in a final sample of 16 companies observedover five years, thus generating 80 observations. Data used in this study weresecondary in nature, obtained from audited financial statements and annual reportspublished by each company. The analytical method applied was panel dataregression with hypothesis testing conducted using the EViews 12 application. Therationale for selecting these variables lies in their theoretical and practicalrelevance, as management compensation may incentivize managers to adopt taxstrategies that optimize company resources, revenue growth reflects the company’sability to expand and generate taxable income, while firm size is often associatedwith greater resources but also with closer scrutiny from regulators. The results ofthe analysis show that, partially, management compensation has a positive effect ontax management, indicating that higher compensation encourages managers toimplement more efficient tax strategies. Revenue growth also has a positive effect ontax management, suggesting that companies experiencing increasing revenues aremore motivated to engage in tax planning to minimize tax burdens. Conversely, firmsize has a negative effect on tax management, implying that larger firms may be lessaggressive in tax planning due to reputational risks and greater oversight.Simultaneously, the three variables—management compensation, revenue growth,and firm size—were found to have a significant joint effect on tax management,highlighting the importance of integrating managerial incentives, companyperformance, and structural characteristics in understanding corporate taxbehavior. Keywords: Management Compensation, Revenue Growth, Firm Size and TaxManagement